Prevalence, risk factors and implication of venous thromboembolism in inflammatory bowel disease - Aljehani, Salman Abdulaziz; Shayani, Rayan Thabet; Alrebh, Asia Hussain; Alrebh, Hind Hussain; Alshaqaqiq, Mohammed Abdullah; Alshehri, Wejdan Fayez; Rayshan, Abdullah Salem Al; Alrayshan, Ali Salem; Aldamkh, Abdulrahman Ali; Almousaalfadagm, Ahmed Ali; Bedaiwi, Lama Abdulrahman (International Journal Of Community Medicine And Public Health, 2022)
Inflammatory bowel disease (IBD) is a chronic inflammatory disease that affects the gastrointestinal system and includes Crohn’s disease and ulcerative colitis. Globally IBD accounts for approximately 84.3 cases per 100,000 persons. A well-known extraintestinal manifestation of IBD that increases morbidity and mortality in IBD patients is venous thromboembolism additionally its association with IBD is growing in importance as a result of the global incidence and prevalence of IBD being on the rise. Patients with IBD have a higher risk of developing venous thromboembolism. Prothrombotic mechanisms that include triggering activation of coagulation, which is partially mediated by weakening of the intestinal barrier and released bacterial components, predispose people with IBD to arterial and venous thrombosis. Clinical characteristics of venous thromboembolism in IBD include an earlier onset, high rates during active and remission stages, greater recurrence rates, and a poor prognosis. Surgery, old age and the use of drugs like corticosteroids or tofacitinib may raise the risk of venous thromboembolism in IBD patients. Post-thrombotic syndrome and a high recurrence incidence following hospital discharge are two long-term effects of venous thromboembolism. IBD outpatients frequently develop venous thromboembolism, hence it is advised that high-risk patients have prophylactic treatment timely. It is essential to keep emphasising on preventing and treating venous thromboembolism in IBD patients appropriately for which further research can be beneficial. The purpose of this research is to review the available information about prevalence, risk factors and implication of venous thromboembolism in IBD.